Magnetic resonance imaging study in a normal Bengal tiger (Panthera tigris) stifle joint - Arencibia, Alberto (BMC Vet Res, 2015)
BACKGROUND: The purpose of this study was to describe the normal appearance of the bony and soft tissue structures of the stifle joint of a Bengal tiger (Panthera tigris) by low-field magnetic resonance imaging (MRI), and the use of gross anatomical dissections performed as anatomical reference. A cadaver of a mature female was imaged by MRI using specific sequences as the Spin-echo (SE) T1-weighting and Gradient-echo (GE) STIR T2-weighting sequences in sagittal, dorsal and transverse planes, with a magnet of 0.2 Tesla. The bony and articular structures were identified and labelled on anatomical dissections, as well as on the magnetic resonance (MR) images. RESULTS: MR images showed the bone, articular cartilage, menisci and ligaments of the normal tiger stifle. SE T1-weighted sequence provided excellent resolution of the subchondral bones of the femur, tibia and patella compared with the GE STIR T2-weighted MR images. Articular cartilage and synovial fluid were visualised with high signal intensity in GE STIR T2-weighted sequence, compared with SE T1-weighted sequence where they appeared with intermediate intensity signal. Menisci and ligaments of the stifle joint were visible with low signal intensity in both sequences. The infrapatellar fat pad was hyperintense on SE T1-weighted images and showed low signal intensity on GE STIR T2-weighted images. CONCLUSIONS: MRI provided adequate information of the bony and soft tissues structures of Bengal tiger stifle joints. This information can be used as initial anatomic reference for interpretation of MR stifle images and to assist in the diagnosis of diseases of this region.